Oxidative Routes to the Heterocyclic Cores of Benzothiazole Natural Products - Blunt, Christopher E.; Nawrat, Christopher C.; LeBozec, Lucille; Liutkus, Mantas; Liu, Yang; Lewis, William; Moody, Christopher J. (Synlett, 2016)
Methyl 6-(2-acetylaminoethyl)-4-hydroxy-benzothiazole-2-carboxylate, the benzothiazole core of the natural product violatinctamine, was prepared in a biomimetic oxidative route from N-acetyldopamine and cysteine methyl ester. In an alternative oxidative cyclization, ethyl 6-benzyloxy-5-methoxybenzo[d]thiazole-2-carboxylate, the heterocyclic core of erythrazole A, was also prepared.
Keywords: heterocycles; natural products; amino acids; quinones; oxidation